The Relationship Of Self-Efficacy And Compliance With Healthy Lifestyle Of Hypertension Patients In Brebes - Fathurozak, Fathurozak; Nugroho, Irmawan Andri; Santoso, Eko Budi (Prosiding University Research Colloquium, 2022)
Background: Hypertension is a comorbid disease that requires a healthier lifestyle by adopting a healthy lifestyle to prevent complications and death. In carrying out a healthy lifestyle, hypertension patients need self-efficacy. Self-efficacy is needed for hypertensive patients to improve health through self-confidence in carrying out a healthy lifestyle. Objectives: Determining the relationship between self-efficacy and adherence to a healthy lifestyle in hypertensive patients in Brebes Regency. Research Methods: This research method the used quantitative descriptive correlation using cross-sectional research design, sampling used purposive sampling. The number of samples in this study were 85 respondents with hypertension in Sridadi Village, Sirampog District, Brebes Regency. Data analysis using univariate and bivariate analysis using Spearman rank. Using a self-efficacy questionnaire 10 questions and healthy lifestyle adherence 15 questions. Results: The results of this study were 77 (90.6%) respondents had good self-efficacy categories and 8 (9.4) respondents had poor self-efficacy. A total of 71 (83.5) respondents have a healthy lifestyle adherence to the obedient category, while 14 (16.5) respondents are in the non-compliant category. Conclusion: There is a significant relationship between self-efficacy and adherence to a healthy lifestyle in hypertensive patients in Brebes Regency, with p value (0.000) p <0.05 with a correlation coefficient of r = 0.601. Recommendation: For further researchers, it will consideration for researching the factors that influence self-efficacy with adherence to a healthy lifestyle in hypertensive patients.